Crystal structure of tris(3-iodopyridin-1-ium) catena-poly[(hexachlorido-κ1 Cl)-(μ2-trichlorido-κ2 Cl:Cl)diantimony(III)], C15H15Cl9I3N3Sb2 - Ma Yuxin; Hao Munan; Sun Ruijin; Jin Shifeng; Zhao Changchun (Zeitschrift für Kristallographie - New Crystal Structures)
C15H15Cl9I3N3Sb2, monoclinic, C2/c (no. 15), a = 28.2633(7) Å, b = 12.4964(3) Å, c = 9.1542(3) Å, β = 99.5840(10)°, V = 3188.04(15) Å3, Z = 4, R gt(F) = 0.0274, wR ref(F 2) = 0.0687, T = 273.15 K.